(untitled) (Emancipação, 2026)
This article examines the implementation of digital technologies and artificial intelligence in public health, focusing on the state of Paraná, in light of Brazil’s Digital Health Strategy (2020-2028), and analyzes their effects on equity of access. The study adopts a qualitative approach, based on documentary and bibliographic research, drawing on official regulations and scientific literature. Findings indicate that digitalization enhances system integration, informational capacity, and potential access particularly in Primary Health Care yet remains constrained by infrastructural inequalities, regulatory gaps in governance and health data protection, and dependence on private actors. The article further discusses platformization processes and the risks of financialization associated with public-private partnerships and data capture. It concludes that digitalization does not, in itself, ensure greater equity; rather, it depends on detailed regulation, robust public governance, and institutional capacity to avoid reproducing inequalities within Brazil’s Unified Health System (SUS).